Assessment of indicators of a kidney blood-groove at chronic pyelonephritis at patients with diabetes 2 types - Turmuchambetova, A.A.; Turgunova, L.G.; Laryushina, Ye.M.; Alina, A.R.; Koichubekov, B.K.; Zhakupova, A.E. (Fundamental and Experimental Biology, 2015)
There was conducted investigation of the nephritic blood circulations in different levels of the nephritic arteries of 90 patients with the 2nd type of diabetes in combination with the chronic pyelonephritis in the phase of exacerbation and remission. There was determined disorder of the nephritic blood circulations in the form of the nephritic blood flow velocity lowering and the increasing of the nephritic vascular resistance in different levels of the nephritic arteries, the expressiveness of which is determined by the activity of the inflammatory process in kidneys.